Development of Android-Based Learning Media With Smartapp Creator Media On The Subject Of Ipa Reproductive Material In Humans Class 9 SMP Negeri 2 Tawangsari - Sulistyono, Yakub Eriyanto; Trisiana, Anita; Sofia Hapsari, Alfonsa Maria (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The research aimed to evaluate the feasibility of Android-based learning tools crafted with Smartapp Creator for Grade 9Science students at Tawangsari State Junior High School 2, focusing on human reproduction. Utilizing the Research andDevelopment (R&D) method with the ADDIE model, the study encompassed phases such as Analysis, Design, andEvaluation. Data was collected via interviews, questionnaires, and documentation. Media validity was gauged by specialists inmedia, subject matter, and local Science teachers. Analysis relied on the Likert scale for media feasibility scores and blackboxtesting. The study’s findings included (1) The Android-based media on human reproduction proved functional and purposeful,affirmed by blackbox testing. (2) Feasibility scores, as determined by media experts, were high. Subject matter specialists ratedit at 96% ("very feasible"), while local Science teachers rated it at 86%.Keywords: Development, Media Learning, Android, Smart Apps Creator, Science, Reproduction in Humans